MANIFESTASI KESETARAAN GENDER DI PERGURUAN TINGGI - Raihan Putry (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2016)
Following the flow of transformation and the times today, the discourse on women's leadership turned out to be growing and getting a response from the community, along with the growth and development of Scientific Management (Scientific). Leadership is no longer based on talent, heritage, experience and the male gender, but more than the physical and mental readiness of men and women in a planned towards professionalism. All the program is done through planning, analysis and development systematically to raise stamina leadership qualities in accordance with the spirit of the Shari'ah. This paper discusses the concept of gender equality in representation in college. First, gender equality is seen as a condition when women are placed on an equal footing and given the same rights and obligations as men. Secondly, gender equality is seen as a condition that is expected to bring about a change for a better life. Both representations of gender equality is highly influenced by the history, background, purpose, and vision and mission of the organization for women. Furthermore, the representation is then manifested in features of managerial college.